2010
DOI: 10.1186/1471-2458-10-553
|View full text |Cite
|
Sign up to set email alerts
|

Trends in HIV & syphilis prevalence and correlates of HIV infection: results from cross-sectional surveys among women attending ante-natal clinics in Northern Tanzania

Abstract: BackgroundSentinel surveillance for HIV in ante-natal clinics (ANC) remains the primary method for collecting timely trend data on HIV prevalence in most of sub-Saharan Africa. We describe prevalence of HIV and syphilis infection and trends over time in HIV prevalence among women attending ante-natal clinics (ANC) in Magu district and Mwanza city, part of Mwanza region in Northern Tanzania. HIV prevalence from ANC surveys in 2000 and 2002 was 10.5% and 10.8% respectively. In previous rounds urban residence, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 20 publications
10
29
1
Order By: Relevance
“…The least prevalence rate (1.6%) occurred among 14-20 years age group. This is in line with a previous Tanzanian study [17] and a report from Ethiopia [18]. However, our prevalence rate in this age group was much lower than what was reported by Kumurya and Sule [18] and Oladeinde et al [19].…”
Section: Resultssupporting
confidence: 93%
“…The least prevalence rate (1.6%) occurred among 14-20 years age group. This is in line with a previous Tanzanian study [17] and a report from Ethiopia [18]. However, our prevalence rate in this age group was much lower than what was reported by Kumurya and Sule [18] and Oladeinde et al [19].…”
Section: Resultssupporting
confidence: 93%
“…However, co-infected women were not more likely to be treated with penicillin. Though there was a small sample size and low prevalence of syphilis documented in the study population, the proportion of women seen to be co-infected is larger than other estimates from Sub-Saharan Africa, with syphilis and HIV co-infection rates of 0.9% and 1.4% being recently observed in Tanzania [21,22]. Introduction of RST testing did not affect facility-level rates of HIV testing uptake for pregnant women, which remained above 77% at all time periods compared.…”
Section: Discussionmentioning
confidence: 58%
“…Population-based studies have found rates of HIV twice as high in informal settlement/peri-urban areas compared to urban and rural areas (Boerma et al, 2002; Coffee et al, 2005; Shisana et al, 2005). In western Kenya, rural beach villages are key migration destinations for women (Camlin et al, 2013), and the eastern African region’s highest HIV prevalence and incidence rates are found in communities surrounding the lake in Kenya and other countries bordering Lake Victoria (Asiki et al, 2011; Kumogola et al, 2010; Kwena et al, 2010). The migration of women within rural Kenya may have been a critical factor in the diffusion of HIV some two decades ago.…”
Section: Introductionmentioning
confidence: 99%